2011
DOI: 10.1017/s003329171100105x
|View full text |Cite
|
Sign up to set email alerts
|

Guideline concordant monitoring of metabolic risk in people treated with antipsychotic medication: systematic review and meta-analysis of screening practices

Abstract: In routine clinical practice, metabolic monitoring is concerningly low in people prescribed antipsychotic medication. Although guidelines can increase monitoring, most patients still do not receive adequate testing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
237
2
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 292 publications
(255 citation statements)
references
References 114 publications
15
237
2
1
Order By: Relevance
“…Risperidone was the SGA most commonly started (43%; n = 6956), followed by aripiprazole (31%; n = 5035), quetiapine (20%; n = 3245), olanzapine (4%; n = 659), and other agents (2%; n = 409). The cohort age distribution included 2% (n = 364) ages 2 to 4 years, 22% (n = 3508) ages 5 to 9, 17% (n = 2738) ages 10 to 12, 26% (n = 4282) ages 13 to 15, and 33% (n = 5412) ages 16 Detailed results of baseline GLU assessment data availability for 14 days before through 3 days after, 90 days before through 3 days after, and 90 days before through 30 days after starting an SGA are shown in Tables 1 and 2. Eleven percent (n = 1858) of youth had GLU assessed between 90 before and 3 days after the first SGA dispensing date.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Risperidone was the SGA most commonly started (43%; n = 6956), followed by aripiprazole (31%; n = 5035), quetiapine (20%; n = 3245), olanzapine (4%; n = 659), and other agents (2%; n = 409). The cohort age distribution included 2% (n = 364) ages 2 to 4 years, 22% (n = 3508) ages 5 to 9, 17% (n = 2738) ages 10 to 12, 26% (n = 4282) ages 13 to 15, and 33% (n = 5412) ages 16 Detailed results of baseline GLU assessment data availability for 14 days before through 3 days after, 90 days before through 3 days after, and 90 days before through 30 days after starting an SGA are shown in Tables 1 and 2. Eleven percent (n = 1858) of youth had GLU assessed between 90 before and 3 days after the first SGA dispensing date.…”
Section: Resultsmentioning
confidence: 99%
“…They documented cardiometabolic monitoring practices had not changed substantially since the FDA warnings, SGA product label revisions, and national monitoring guidelines issuance. Mitchell et al 16 recently conducted a systematic review and meta-analysis of international studies of metabolic monitoring, including studies published before and after formal monitoring guidelines were available. They too found that suboptimal metabolic monitoring among patients prescribed SGAs continued after guidelines were published.…”
Section: (Continued On Last Page)mentioning
confidence: 99%
“…Some of the possible barriers to screening in practice include uncertainty as to whether such physical health screening was the responsibility of the psychiatric team rather than a primary care clinician [20], a lack of confidence in the interpretation of abnormal screening results [21] and limited access to basic infrastructure such as IT equipment [22]. Other possible explanations for the relatively low level of screening is that clinicians may target patients for the assessment of metabolic side effects rather than routinely screen all patients prescribed antipsychotic medication.…”
Section: Discussionmentioning
confidence: 99%
“…Our group reviewed 38 studies, involving 217 539 patients, that examined routine monitoring of patients taking anti psychotics before the implementation of explicit guidelines (Mitchell 2012). Across all baseline studies, routine monitoring rates were generally low but were highest for blood pressure (67%) and triglycerides (60%).…”
Section: Medical Care and Metabolic Monitoring In Psychiatric Settingsmentioning
confidence: 99%